2018
DOI: 10.1111/obr.12717
|View full text |Cite
|
Sign up to set email alerts
|

The association between antibiotic use in infancy and childhood overweight or obesity: a systematic review and meta‐analysis

Abstract: Antibiotic exposure in infants, aged < 24 months, was associated with a small increase in odds of childhood overweight or obesity in some subgroups of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 51 publications
2
58
3
Order By: Relevance
“…11 However, there is concern that previous positive studies have not adequately accounted for potential confounders, including genetic and environmental factors. [8][9][10] In particular, very few studies have examined siblings or twins to account for possible unmeasured confounders, and the studies that did include these analyses reported no associations between antibiotic exposure and risk of childhood obesity. 5,6,12 Nonetheless, these studies were not without limitations, because they consisted of small cohorts and did not include national data or analyses on both siblings from singleton pregnancies (henceforth referred to as "siblings") and those from multiple pregnancies (henceforth referred to as "twins").…”
Section: Introductionmentioning
confidence: 99%
“…11 However, there is concern that previous positive studies have not adequately accounted for potential confounders, including genetic and environmental factors. [8][9][10] In particular, very few studies have examined siblings or twins to account for possible unmeasured confounders, and the studies that did include these analyses reported no associations between antibiotic exposure and risk of childhood obesity. 5,6,12 Nonetheless, these studies were not without limitations, because they consisted of small cohorts and did not include national data or analyses on both siblings from singleton pregnancies (henceforth referred to as "siblings") and those from multiple pregnancies (henceforth referred to as "twins").…”
Section: Introductionmentioning
confidence: 99%
“…Multiple baseline risks can be presented to decision makers so that different recommendations can be made for different populations. Software from the GRADE (grading of recommendations, assessment, development, and evaluation) Working Group (GRADEPro, McMasters University, Hamilton, Ontario, Canada) enables different absolute effects to be calculated and presented to help decision makers 21…”
Section: Conversion To Binary Relative and Absolute Measuresmentioning
confidence: 99%
“…Long-term use of antibiotics, especially early in life, has been linked with obesity, allergies, and other chronic disorders [6][7][8][9]. In the Nurses' Health Study (NHS), selfreported retrospective history of antibiotic use has been linked to increased risk of colorectal adenoma [10].…”
Section: Introductionmentioning
confidence: 99%